On People, Sensorial Perception, and Potential Affinity in Southern Chile. Issue 2 (1st June 2019) - Bonelli, Cristóbal
Abstract : Through an ethnographic exploration of Pehuenche conceptualizations of doubles and of greeting and funerary practices in Southern Chile, this article considers the ontological relevance of sensorial perception as a main operator for stabilizing the tension between autonomy and dependence on otherness. The article aims to establish how relations between 'real people' or che, in Pehuenche daily life, do not precede mutual sensorial perception; instead, they can be seen as the result of such perceptions. In so doing, and building upon the concept of 'potential affinity' as a persisting relational principle of relatedness, I show how the minimal unit of analysis of sensorial perception is not composed of separated unities. Rather, it is an assemblage of multiple capacities involving both visible and invisible relational entities.